MicroRNAs in Methamphetamine-Induced Neurotoxicity and Addiction - Deng, Bi; Zhang, Zhirui; Zhou, Huixuan; Zhang, Xinran; Niu, Shuliang; Yan, Xisheng; Yan, Jie (Frontiers in Pharmacology, 2022)
Methamphetamine (METH) abuse remains a significant public health concern globally owing to its strong addictive properties. Prolonged abuse of the drug causes irreversible damage to the central nervous system. To date, no efficient pharmacological interventions are available, primarily due to the unclear mechanisms underlying METH action in the brain. Recently, microRNAs (miRNAs) have been identified to play critical roles in various cellular processes. The expression levels of some miRNAs are altered after METH administration, which may influence the transcription of target genes to regulate METH toxicity or addiction. This review summarizes the miRNAs in the context of METH use, discussing their role in the reward effect and neurotoxic sequelae. Better understanding of the molecular mechanisms involved in METH would be helpful for the development of new therapeutic strategies in reducing the harm of the drug.